GOAL-BASED TEACHING MANAGEMENT METHODS - Ishankulova, Diyora (Журнал иностранных языков и лингвистики, 2023)
Our article will consider techniques for most teachers who believe that a communicative approach to language teaching and learning in particular are questionable ideas. The truth is that the approach rests on a single core philosophy that should guide everything we learn and will learn. Teachers must demonstrate practical results. In other words, the student must be able to practice the same thing and, if necessary, transfer what has been learned to other language skills. Teaching is a two-way process. It is often argued that if there is no education, there is no education. It is also known that teaching and learning is a lifelong process.